ARCHAEOLOGICAL AND HISTORICAL ORIGINS OF THE PARANJA: FROM ANCIENT FARAJI TO CENTRAL ASIAN VEIL TRADITIONS - Sobirov Sardor Alisher o‘g‘li; Sobirova Nodirebagim Zoir qizi (TADQIQOTLAR, 2025)
Annotation: This article examines the historical development of the paranja, a traditional women’s garment of Central Asia. Based on archaeological and historical evidence, it traces its origin from the ancient faraji to later Islamic and Soviet forms. The  study  highlights  the  paranja  as  both  a  cultural  and  social  symbol,  reflecting changes in religion, aesthetics, and women’s status throughout Central Asian history.